Informed Consent as a Fundamental Right of Patients: The Law and Medical Ethics Perspective - Chairul Z; Hardyansah, Rommy; Suwito; Waskito, Sarwo; Khayru, Rafadi Khan (Journal of Social Science Studies, 2023)
In the era of globalization, the health sector has undergone significant changes, especially in providing information on medical service risks to patients. This information is a basic right of patients to understand their health conditions and make appropriate medical decisions. Practices in the field show that this right is often not fulfilled, resulting in physical, psychological, and economic losses for patients. The right to information about medical risks has a strong law basis and is the foundation for patients in providing informed consent, which is an important element in medical treatment. A doctor's negligence in providing information can have serious law consequences, both through civil lawsuits based on Article 1365 of the Civil Code and criminal charges under Articles 351 and 359 of the Criminal Code. This research aims to examine how patients' rights to information about medical risks are regulated and implemented, as well as to analyze the law sanctions that can be imposed on doctors who do not fulfill these obligations. With a normative approach, this research seeks to contribute to strengthening lawful protection for patients and increasing the accountability of doctors in meeting applicable ethical and law standards.